Effects of different roasting parameters on selected physicochemical properties and sensory evaluation of coffee beans / Nur Fatin Najihah Md Sobri... [et al.] - Md Sobri, Nur Fatin Najihah; Mohd Nazri, Nur Fazliana; Sumani, Nurpatin Syuhada; Azaman Shah, Nurul Adlin; Mohamad, Naemaa; Hajar, Nadya (Universiti Teknologi MARA, Negeri Sembilan, 2019)
Arabica coffee beans from the same origin were roasted at three different roasting parameters namely minimum roasting (180°C), medium roasting (220°C) and maximum roasting (260°C) each for 20 minutes in order to investigate the changes in the physical, chemical and sensorial evaluation. During the roasting process, the coffee beans becomes more brittle due to the chemical, physical and structural modifications. There are limited studies reported for coffee beans that have been roasted with different roasting parameters in term of selected physicochemical properties and sensory evaluation. The roasted coffee beans oil was extracted by using Soxhlet Extraction method for 8 hours. The objective of this study was to determine the effects of different roasting parameters on selected physicochemical properties and sensory evaluation of coffee beans in the term of: moisture content (%), oil extraction (%), peroxide value (mEq/kg), acid value (mg KOH/g), furan (absorbance) and sensory evaluation. The furan (abs) content was recorded as 0.24 ± 0.04 (minimum roasting), 0.69 ± 0.03 (medium roasting) and 0.91 ± 0.01 (maximum roasting). In terms of sensory evaluation, most participants preferred coffee drink made from medium roasted coffee beans for aroma, colour, sweetness, flavour and overall criteria. Meanwhile, for the acidity and bitterness criteria, the participants preferred coffee drink made from maximum roasted coffee beans. As a conclusion, roasting temperature is the main factor that influences the physicochemical properties and sensory evaluation of coffee beans.